Then I received the habit of holy religion: Memorializing the Monastic Profession at the Turn of the Twelfth Century - Vanderputten, St (Sacris erudiri, 2010)
By looking at the archives of the Benedictine priory of Saint-Georges in the Northern French town of Hesdin, this paper aims to illustrate the versatility of a monastic community at the turn of the twelfth century in documenting the spiritual, legal and memorial implications of the monastic profession, as well as their understanding of the ritual itself as a significant social event, in which lasting ties were established with secular society. The analysis of an exceptional notice relating to the conversion of a man named Walter will show how, in addition to these purposes, the written word could also be used to capture in a permanent form the profession ritual as a ‘total’ transition of a layman’s properties and self from the secular world to its spiritual counterpart.